2023
DOI: 10.1002/adfm.202212627
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Substrate‐Structured Sb2S3 Solar Cells with Back Interface Selenization

Abstract: Antimony sulfide (Sb2S3) with a 1D molecular structure has strong bending characteristics, showing great application potential in flexible devices. Herein, the flexible substrate‐structured Sb2S3 solar cells is developed and improve device performances by the back interface selenization. The high‐quality Sb2S3 film with an optimal thickness of 1.8 µm, ensuring efficient spectra utilization, is deposited on flexible Mo foils by the rapid thermal evaporation technique. To solve the issues of back interfacial rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…As such, we focused on Sb 2 S 3 , a q-1D vdW phase that belongs to a family of earth-abundant Pn 2 Ch 3 pnictochalcogenides (Pn = pnictogen, e.g., Sb and Bi; and Ch = chalcogen, e.g., S and Se) (Figure ). These phases have been heavily studied due to their optical and electronic properties, which include visible-to-near-infrared band gaps reported in the 1.1 to 1.8 eV range and substantial optical absorption coefficient suitable for thin-film solar energy conversion devices. More recently, studies have shown that the photovoltaic efficiencies of thin films based on Sb 2 S 3 are strongly dependent on the crystallographic orientation of the polycrystalline domains, implying that the physical properties of these pnictochalcogenides are inherently tied to their morphologies and nanocrystalline structures. Encouragingly, numerous computational studies have predicted the size- and orientation-dependent indirect-to-direct band gap crossover in Sb 2 S 3 upon confinement due to the small energy differences in the conduction band states along and across the chains. …”
Section: Resultsmentioning
confidence: 99%
“…As such, we focused on Sb 2 S 3 , a q-1D vdW phase that belongs to a family of earth-abundant Pn 2 Ch 3 pnictochalcogenides (Pn = pnictogen, e.g., Sb and Bi; and Ch = chalcogen, e.g., S and Se) (Figure ). These phases have been heavily studied due to their optical and electronic properties, which include visible-to-near-infrared band gaps reported in the 1.1 to 1.8 eV range and substantial optical absorption coefficient suitable for thin-film solar energy conversion devices. More recently, studies have shown that the photovoltaic efficiencies of thin films based on Sb 2 S 3 are strongly dependent on the crystallographic orientation of the polycrystalline domains, implying that the physical properties of these pnictochalcogenides are inherently tied to their morphologies and nanocrystalline structures. Encouragingly, numerous computational studies have predicted the size- and orientation-dependent indirect-to-direct band gap crossover in Sb 2 S 3 upon confinement due to the small energy differences in the conduction band states along and across the chains. …”
Section: Resultsmentioning
confidence: 99%
“…Amorphous Sb 2 S 3 Film Deposition: The amorphous Sb 2 S 3 films were deposited on the clean substrates using the RTE vacuum equipment (OTF-1200X) at low deposition temperature. [27,44] The Sb 2 S 3 powder (98%, Aladdin Industrial Corporation) with 0.4 g was uniformly sprinkled on the clean glass as an evaporation source. The substrate covered by a graphite block was face-down mounted on the top.…”
Section: Methodsmentioning
confidence: 99%
“…12–15 In addition to generic power production (terawatt levels), Sb 2 X 3 solar cells are well suited for integration in futuristic, lightweight, flexible, and wearable electronic devices. 15–18…”
Section: Introductionmentioning
confidence: 99%